Accelerometer-assessed physical activity and incident diabetes in a population covering the adult life span: the Hispanic Community Health Study/Study of Latinos. Issue 5 (10th September 2020) - Chen, Guo-Chong; Qi, Qibin; Hua, Simin; Moon, Jee-Young; Spartano, Nicole L; Vasan, Ramachandran S; Sotres-Alvarez, Daniela; Castaneda, Sheila F; Evenson, Kelly R; Perreira, Krista M; Gallo, Linda C; Pirzada, Amber; et al.
ABSTRACT: Background: The association between accelerometer-assessed physical activity and risk of diabetes remains unclear, especially among US Hispanic/Latino adults who have lower levels of physical activity and a higher diabetes burden compared with other racial/ethnical populations in the country. Objectives: To examine the association between accelerometer-assessed physical activity and incident diabetes in a US Hispanic/Latino population. Methods: We included 7280 participants of the Hispanic Community Health Study/Study of Latinos who aged 18–74 y and free of diabetes at baseline. Data on moderate-to-vigorous physical activity (MVPA) were collected using a 7-d accelerometer measurement. Incident diabetes was assessed after a mean ± SD of 6.0 ± 0.8 y using standard procedures including blood tests. RRs and 95% CIs of diabetes associated with MVPA were estimated using survey Poisson regressions. The associations of MVPA with 6-y changes in adiposity measures were also examined. Results: A total of 871 incident cases of diabetes were identified. MVPA was inversely and nonlinearly associated with risk of diabetes ( P -nonlinearity = 0.006), with benefits accruing rapidly at the lower end of MVPA range (<30 min/d) and leveling off thereafter. The association differed by population age ( P -interaction = 0.006). Higher MVPA was associated with lower risk of diabetes among individuals older than 50 y (RRQ4 versus Q1  = 0.50; 95% CI: 0.35, 0.73; P -trend < 0.001) but not among younger individuals (RRQ4 versus Q1  = 0.98; 95% CI: 0.66, 1.47; P -trend = 0.92). An inverse association between MVPA and 6-y gain in waist circumference was also limited to the older group ( P -interaction with age < 0.001). Conclusions: Among US Hispanic/Latino adults, baseline accelerometer-derived MVPA was inversely associated with incident diabetes only among individuals aged 50 y and older. Further studies are needed to confirm our findings and to clarify potential mechanisms underlying the possible age differences in the MVPA–diabetes association. This study was registered at clinicaltrials.gov as NCT02060344.